Online engagement as a multimodal discursive practice: The case of Dubai Cares' Facebook page. (January 2021) - Ben Moussa, Mohamed; Benmessaoud, Sanaa
The paper examines the role of social media platforms in public relations engagement, focusing on the case of a leading non-profit organization in the UAE, namely Dubai Cares. Drawing on multimodal critical discourse analysis (MCDA), the paper analyses the textual, paratextual, and visual modes of communication deployed by the organization, and investigates their role as (multimodal) discursive practices in constructing engagement and shaping power relations between the organizations and its publics. A key finding of the paper is that Dubai Cares' online public relations efforts to promote its international recognition and legitimacy often come at the expense of addressing multiple power differentials between the organization and its stakeholders. The paper demonstrates how approaching engagement as a multimodal discourse, where power relations are at play, helps transcend the limitations of instrumental interpretations of the notion of engagement, thus obscuring its inherent discursive and social dimension.